Ônus da prova e a dispensa discriminatória - Wagner, Jorge da Silva (2017)
The purpose of this work is to study the application of the theory of dynamic assignment of the burden of proof on Labour Procedural Law aiming to prevent injustices arising from prejudiced discrimination. Prejudice is brought to light under various pretexts such as race, gender, age, religion, social class, political preference, sexual orientation, etc. Negative discrimination is one of the sides of prejudice, detrimental to a particular group of people or an individual due to the creation of unfair situations. Within the scope of the labour law, this aspect of prejudice is associated with dismissal motivated by a discriminatory behaviour of an employer against his/her employee, and results in the obligation to reinstate the employee and, consequently, pay the amounts connected to his/her dismissal period, pain and suffering compensation, and even the payment of double wages. According to articles 373 of the Code of Civil Procedure and 818 of the Consolidation of the Brazilian Labour Laws, which has its grounds on a static view, the evidence of the allegations lies on the party that makes them. However, the dynamic theory of the burden of proof tears the static conception of the assignment of such burden, taking into account the process in its tangible reality, attributing the burden of proof to the party who, due to factual circumstances, has better conditions to demonstrate the events of the specific case, regardless of his/her/its position. Based on the study conducted, it was possible to conclude that, in the labour law context and despite the fact that the Consolidation of the Brazilian Labour Laws adopts the static view, the dynamic theory of the burden of proof may be applied, in light of the principle of equality, court’s instructive powers, collaboration of the parties and good faith. Finally, the shifting of the burden of proof has been proven to occur at different times, but, nevertheless, the most appropriate time will be during the evidentiary phase, avoiding surprises and ensuring the right to contest. The study was conducted in line with the bibliographical, qualitative, and partially exploratory methodology